The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1158/1078-0432.ccr-15-2429
|View full text |Cite
|
Sign up to set email alerts
|

Voxel Level Radiologic–Pathologic Validation of Restriction Spectrum Imaging Cellularity Index with Gleason Grade in Prostate Cancer

Abstract: Purpose: Restriction spectrum imaging (RSI-MRI), an advanced diffusion imaging technique, can potentially circumvent current limitations in tumor conspicuity, in vivo characterization, and location demonstrated by multiparametric magnetic resonance imaging (MP-MRI) techniques in prostate cancer detection. Prior reports show that the quantitative signal derived from RSI-MRI, the cellularity index, is associated with aggressive prostate cancer as measured by Gleason grade (GG). We evaluated the reliability of RS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…A novel MRI acquisition protocol named restriction spectrum imaging (RSI) may be able to parse the signal of inflammation and cancer [15]. RSI-MRI in the prostate has specifically been shown to be more accurate than ADC values, improve tumor conspicuity, and alter signal between inflammation and cancer [16171819]. Other groups have investigated more efficient use of intravenous contrast enhancement techniques to distinguish aggressive tumors [20].…”
Section: Discussionmentioning
confidence: 99%
“…A novel MRI acquisition protocol named restriction spectrum imaging (RSI) may be able to parse the signal of inflammation and cancer [15]. RSI-MRI in the prostate has specifically been shown to be more accurate than ADC values, improve tumor conspicuity, and alter signal between inflammation and cancer [16171819]. Other groups have investigated more efficient use of intravenous contrast enhancement techniques to distinguish aggressive tumors [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies applied a focal boost dose to sub-volumes identified as abnormal regions on quantitative images [ 7 , 14 , 50 , 60 ], including the FLAME-trial [ 37 ]. However, the use of sub-volumes means discretisation of tumour characteristics such as clonogen density and hypoxia, whereas typically these characteristics vary continuously throughout the gland [ 1 , 21 , 41 , 42 , 68 ]. In studies where voxel-level information was utilised, simple linear relationships between image intensities and doses were frequently assumed [ 3 , 14 , 60 ], or non-validated dose prescription functions were used [ 4 , 18 , 31 , 38 , 48 , 52 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…On a voxel‐by‐voxel basis, RSI CI was significantly different among benign (mean RSI cellularity index = 0.16), low grade (mean score = 1.15) and high grade disease (mean score = 1.52) with increasing cellularity index correlating to increasing Gleason grade. Thus RSI CI correlates with Gleason grade at the voxel level, reflecting variation within individual tumors …”
Section: Interpretation Of Prostate Mri With Rsi: Existing Datamentioning
confidence: 97%
“…Thus RSI CI correlates with Gleason grade at the voxel level, reflecting variation within individual tumors. 55…”
Section: In Vivo Characterizationmentioning
confidence: 99%